High-Resolution Imaging of Radio Interference - Kuang, Zhujia (Transactions on Computer Science and Intelligent Systems Research, 2024)
In recent years, the advancement of radio astronomy has played a critical role in the exploration of space. The development of large-scale radio telescopes, such as the Five-hundred-meter Aperture Spherical Telescope (FAST) in China, has enabled astronomers to capture high-resolution images of celestial bodies and improve people’s understanding of the universe. However, challenges remain in achieving higher precision and sensitivity in astronomical observations. This review paper provides an overview of the fundamental principles, methodologies, and applications of radio interferometers, particularly focusing on their ability to enhance the resolution of astronomical images through synthetic aperture technology. The paper discusses the structural components of radio telescopes and details the operation of radio interferometers, including their application in Very Long Baseline Interferometry (VLBI). By examining the technological developments in VLBI and space VLBI, this paper highlights their contributions to astronomical observations and explores future directions for radio interferometry research. Future research may consider further improving the capabilities and applications of high-resolution radio imaging.